2014
DOI: 10.1121/1.4845355
|View full text |Cite
|
Sign up to set email alerts
|

Modeling propagation of infrasound signals observed by a dense seismic network

Abstract: The long-range propagation of infrasound from a surface explosion with an explosive yield of about 17.6 t TNT that occurred on June 16, 2008 at the Utah Test and Training Range (UTTR) in the western United States is simulated using an atmospheric model that includes fine-scale layered structure of the wind velocity and temperature fields. Synthetic signal parameters (waveforms, amplitudes, and travel times) are calculated using parabolic equation and ray-tracing methods for a number of ranges between 100 and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Background pressure and density profiles [Eq. (4)] are the same as in a motionless atmosphere. 13 Under the assumptions made above, variations of the sound speed c 0 and the scale height h have the same representative spatial scale L as the temperature T 0 .…”
Section: Derivation Of Agw Dispersion Relationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Background pressure and density profiles [Eq. (4)] are the same as in a motionless atmosphere. 13 Under the assumptions made above, variations of the sound speed c 0 and the scale height h have the same representative spatial scale L as the temperature T 0 .…”
Section: Derivation Of Agw Dispersion Relationsmentioning
confidence: 91%
“…Accurate modeling of wave dissipation is important in a wide range of problems from understanding the momentum and energy transport by waves into the upper atmosphere 1 to predicting long-range propagation of infrasound [2][3][4] to the acoustic remote sensing of mesospheric and thermospheric winds. 5,6 Variations with height of the mass density, kinematic viscosity, and other physical parameters of the atmosphere have a profound effect on the wave dissipation and its frequency dependence.…”
Section: Introductionmentioning
confidence: 99%
“…location estimation will be peak times, as the onset is not always easily determined. Therefore, although the model matches well in most range bins and is acceptable for use now, it would be better to implement small-scale structures into the G2S profiles in the future to acquire more accurate model fits, as was demonstrated in other studies (e.g., Hedlin and Walker, 2013;Drob et al, 2013;Chunchuzov et al, 2014). It is worth noting that the GeoAc simulations for 1 August 2007 and 1 August 2010 with the same ray-shooting parameters (azimuth and inclination angle) are in very good agreement, and so the model is translatable over different years during the same month/daytime period.…”
Section: Comparison Of Regional Physics-based Model and Data Priorsmentioning
confidence: 91%
“…They showed that by adding small-scale gravity wave perturbations to the G2S profiles, the newly predicted arrivals were more delayed and spread out in time, matching the complete duration of the signal, and also occurred at more extended ranges into areas that were previously predicted as shadow zones, but that contained observed arrivals (Hedlin and Walker, 2013;Drob et al, 2013;Hedlin and Drob, 2014). Chunchuzov et al (2014) was also able to predict arrivals that penetrate the shadow zone and other ranges that contain multiple stratospheric branches not predicted by smooth G2S profiles, as well as increased durations, by implementing range-dependent fluctuations in a single G2S profile with a pseudodifferential parabolic equation method. Finally, we note that the observed data was analyzed by picking the largest peak in the signal, which was not necessarily the first or only acoustic phase arrival of the signal.…”
Section: Comparison Of Regional Physics-based Model and Data Priorsmentioning
confidence: 97%
“…In addition to the vertical large-scale gradients of atmospheric properties, which are largely controlled by the solar radiative heating, large-scale waves, and tides and by gravity waves (GWs) and their momentum forcing, localized small-scale turbulent perturbations are also ubiquitous in the Earth's atmosphere (Bossert et al, 2015;Fritts & Alexander, 2003;Fritts et al, 2018;Hecht et al, 1997;Tsuda, 2014). Such fluctuations not only are responsible for partial reflections and scattering of the IAW signals (Chunchuzov et al, 2011(Chunchuzov et al, , 2013(Chunchuzov et al, , 2014(Chunchuzov et al, , 2015 but can also amplify or weaken the various acoustic waveguides and in particular the stratospheric duct (Bertin et al, 2014;Lalande & Waxler, 2016). One of their most important causes is the breaking of GWs.…”
Section: 1029/2019gl082456mentioning
confidence: 99%